Fungal Diseases in Pistachio Cultivation: Assessing Their Impact on Yield and Quality through Types, Symptoms, and Management Strategies - Nazarova, Odina (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This article explores the major fungal diseases affecting pistachio cultivation, detailing their types, symptoms, and impacts on yield and nut quality. Particular attention is given to pathogens such as Alternaria, Botryosphaeria, Phytophthora, and Verticillium, which significantly threaten tree health and productivity. The paper also discusses current management strategies, including cultural practices, chemical fungicides, and biological control methods within Integrated Disease Management (IDM) frameworks. Findings indicate that fungal infections can cause yield losses of up to 30% under poor agronomic conditions. Emphasis is placed on the necessity for sustainable and multifaceted approaches to ensure long-term productivity and profitability in pistachio farming systems.